Cultural Streetscape: Its Value-System, Space and Significance in Oyo Town, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2024)
Cultural streetscape is a remarkable street scene that embodies the local culture. It helps in defining and defending urban forms, improves the physical, economic, and socio-cultural mechanisms of urban streets, provides street views for buildings, and shares communal activities and identities. Streetscape is a significant and multi-dynamic component of urban design that contributes to the success of cities and towns. However, as a result of constant urbanization and neglect, African streets that were previously sites of different cultural expressions and local beliefs are quickly turning into areas devoid of local values and meaning. More so, the significance of a cultural streetscape that facilitates ingenious street views, solves ecological challenges, and retains the local memory of places is becoming scarce in the literature. Through an in-depth interview, analysis of pertinent academic outputs, and firsthand observation of the core residential areas of Oyo town, this study revealed the value and significance of cultural streetscape in building, shaping, preserving and sustaining local place identity. Proper archiving and infusion of cultural streetscape elements into the old and new streets design are necessary to ensure Yoruba place identity does not completely become void.